Two-Dimensional Software Defect Models with Test Execution History. (14th November 2012) - Ishii, Tomotaka; Dohi, Tadashi
Abstract : In general, the software-testing time may be measured by two kinds of time scales: calendar time and test execution time. In this paper, we develop two-dimensional software reliability models with two-time measures and incorporate both of them to assess the software reliability with higher accuracy. Since the resulting software defect models are based on the familiar nonhomogeneous Poisson processes with two time scales, which are the natural extensions of one-dimensional software defect models, it is possible to treat the time data both simultaneously and effectively. We investigate the dependence of test-execution time as a testing effort on the software reliability assessment and validate quantitatively the software defect models with two-time scales. We also consider an optimization problem when to stop the software testing in terms of two-time measurements.